A New Mathematical Model For Assessment of Memorization Dynamics - Stepanov, Igor I.; Abramson, Charles I. (The Spanish Journal of Psychology, 2005)
A new memory model is proposed based on regression analysis and exponential- shaped learning curves. The efficacy of the model is tested with several types of experiments including food aversion in snails, maze learning in rats and memory tests for adults and children. The model is also tested on drug abusers and alcoholics. The results of goodness of fit tests indicate that our model can accurately be used to predict the memory dynamics of diverse experiments and populations. The model can also be used to predict both group and individual performance. The application of the model to detect memory impairment is discussed, as are limitations